The Sikka Arts Council "Waniana" Logo Analysis - Minggo, Frenomena; Hidayatullah, Taufan (ARTic, 2025)
The Sikka Arts Council “Waniana” has a logo. The logo of the Sikka Arts Council (Waniana) has a meaning embedded within it, and it needs to be analyzed to understand what hidden meanings are contained in the symbol, such as the form of the symbol used. This analysis is based on Alina Wheeler's theory of brand ideals, which includes aspects such as vision, meaning, authenticity, coherence, flexibility, commitment, value, differentiation, and longevity. This study aims to analyze the form elements of the Sikka Arts Council “Waniana” logo to understand the philosophical meaning embedded in its design. The results of the study indicate that the Sikka Arts Council (Waniana) logo effectively represents the community's identity through brand ideals elements and visual identity that reflect local culture. As a result, the Waniana logo integrates local cultural elements, such as the utang oi woven fabric motif, into a modern design, which is a strategic step to preserve cultural heritage in a contemporary context. Keywords: Art Council, Brand Ideals, Logo, Sikka, Visual Identity